Empowering Women in Business : A Mentoring Programme's Impact on Career Advancement - Motalíková, Teťjana; Matysová, Kamila; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the impact of the Equilibrium mentoring programme on the career progression of female participants, focusing on one-to-one sessions, networking event attendance, and financial self-contribution. Through qualitative interviews and a survey of 293 respondents, the study identifies key success factors and evaluates the programme’s effectiveness in supporting women’s professional growth. The findings indicate that the programme contributes positively to career advancement by enhancing confidence, promoting personal growth, and expanding professional networks. While no significant impact was found from session frequency or financial contribution, networking event participation was positively correlated to perceived career progress. The study also addresses challenges such as gender bias and work-life balance and highlights mentors' altruistic motivation to join the programme.
Vedoucí práce: Kamila Matysová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses